Comparison between non-invasive methods and liver histology to stratify liver fibrosis in obese patients submitted to bariatric surgery. Issue 2 (March 2021) - Didoné Filho, Celso Nilo; Reginatto, Cleiton Jonei; Ivantes, Cláudia Alexandra Pontes; Strobel, Rodrigo; Percicote, Ana Paula; Petenusso, Marcio; Sobreira da Silva, Cicero Jordan R.; Benjamim, Cicero Jonas R.; Radominski, Rosana Bento
Abstract: Background: Obesity is a multifactorial disease characterized by fat accumulation, usually associated with non-alcoholic fatty liver disease, which can lead to advanced fibrosis or even cirrhosis. Bariatric surgery (BS) is a treatment approved for weight loss in morbidly obese patients. However, complications from this modality of treatment have been reported and liver cirrhosis connotes more risk procedure. Aims: Evaluate non-invasive methods transient elastography (THE) and scores to establish the degree of liver fibrosis in patients submitted to BS, comparing their performance with liver histology. Methods: We calculated liver fibrosis by non-invasive scores AST to platelet ration index (APRI), fibrosis-4 (FIB-4) and non-alcoholic fatty liver disease (NAFLD) score and THE before and 6 months after the bariatric surgery. The results were compared to liver histology. Results: We included 85 patients, 69.4% females, with a mean age of 36 years, with a mean body mass index (BMI) of 41 kg/m 2 . The non-invasive scores were able to exclude clinically significant fibrosis in 85.9% (APRI) and advanced fibrosis in 96.5% (FIB-4) and 51.8% (NAFLD score). When comparing with the histological findings, the correlation with elastography was 45.9% for the same degree of fibrosis, with high negative predictive value (94.4%) in pre-surgical analysis. In the post-surgical analysis, the correlation with histology was 69.4% for THE and the negative predictive value to exclude clinically significant fibrosis was 98.5%. Conclusion: THE showed low correlation with histology in the pre-surgical analysis. All the methods had better results in post bariatric evaluation comparing with pre-bariatric data and the non-invasive FIB-4 score showed the best of them.